Impacts of cultivations of oasis-basins on food safety of populations: A case study of the basin of Guirsilik in the township of Goudoumaria - Kanembou Lawandi; Malam Assane Maigari; Malam Bourna Bagale Mamadou (European Scientific Journal, ESJ, 2024)
In the township of Goudoumaria, the oasis basins are areas of high agricultural value, although these basins are nowadays mostly degraded or in the process of being degraded, due to a combination of human practices and the effects of climate change. The main objective of this study is to understand the socio-economic and food impact of farming in the basin of the village of Guirsilik. To this end, a methodological approach comprising both theoretical and practical aspects is adopted. The theoretical approach, which consisted of a literature review, revealed that the basins are the main sources of income for the people of the commune of Goudoumaria. Individual and focus group surveys were carried out among farmers to collect data and measure the economic and financial profitability of farming in the Guirsilik basin. Short-cycle crops (onions and cabbage) have proved to be more profitable than long-cycle crops such as manioc and sugar cane. The majority of agricultural products in the basin is used for own consumption (70%) rather than for sale (30%), and around fifty-seven percent (57%) of the produce sold is sold on local markets. Despite its importance for the survival of the population, this basin remains under constant threat of silting up, as well as flooding, depending on the year.